Analysis of transcriptome and chromatin accessibility changes during the differentiation of human embryonic stem cells into neural progenitor cells - LI Linying; CAI Xiaodong; TONG Ran; YANG Chen; WANG Zhiming; HE Xiaoyu; MA Ziyue; ZHANG Feng; LI Lingjie; ZHOU Junmei (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To investigate the changes in transcriptome and chromatin accessibility during the differentiation of human embryonic stem cells (hESCs) into neural progenitor cells (NPCs) using in vitro differentiation models and high-throughput multi-omics sequencing technologies.Methods·hESCs were first induced to differentiate into NPCs in vitro using the embryoid body formation method, and cells at both stages were collected. The cell phenotypes were identified by reverse transcription-quantitative real-time PCR (RT-qPCR) and immunofluorescence (IF) staining. Transcriptome sequencing (RNA-seq) was conducted to detect and analyze the differentially expressed genes (DEGs) between hESCs and NPCs. The assay for transposase-accessible chromatin with high-throughput sequencing (ATAC-seq) was employed to assess chromatin accessibility changes between hESCs and NPCs. Motif enrichment analysis was performed on differentially accessible chromatin regions to discover potential regulatory transcription factors. Finally, an integrated analysis of RNA-seq and ATAC-seq data and the protein-protein interaction (PPI) network were performed to identify key genes and regulatory pathways involved in the early stages of neural differentiation in vitro.Results·Both RT-qPCR and IF results indicated that the expression levels of pluripotency markers (NANOG and POU5F1) were high at the hESC stage but significantly decreased at the NPC stage, while early neural differentiation markers (PAX6, SOX1, and NES) were minimally expressed at the hESC stage but markedly upregulated at the NPC stage. RNA-seq analysis revealed that compared to the hESC stage, there were 5 597 genes upregulated and 3 654 genes downregulated at the NPC stage. Gene function enrichment analysis showed that the upregulated genes at the NPC stage were enriched in the functions related to neural development. ATAC-seq analysis demonstrated a total of 27 491 genomic regions had significant changes in chromatin accessibility during the differentiation from hESC to NPC, with 12 381 regions showing increased accessibility and 15 110 regions showing decreased accessibility. Motif enrichment analysis revealed that transcription factor genes such as DLX1 and LHX2 might play an important role in the differentiation process from hESCs into NPCs. Integrated analysis of RNA-seq and ATAC-seq data revealed that overlapping genes with high expression at the NPC stage were mainly enriched in axon guidance, forebrain development, and neuron migration. After neural differentiation, the expression levels of CTNND2 and LHX2 genes increased, and the chromatin accessibility of related genomic regions also increased. PPI network analysis indentified candidate downstream genes including PRKACA, CDH2, and ERBB4.Conclusion·The in vitro differentiation model of hESCs combined with high-throughput multi-omics sequencing technologies can be used to depict the changes in transcriptome and chromatin accessibility during the differentiation of hESCs into NPCs. In this process, the expression levels of genes related to axon guidance, forebrain development, and neuronal migration pathways increase and related chromatin accessibility is enhanced.